Measurement of magnetic susceptibility in pulsed magnetic fields using a proximity detector oscillator. - Ghannadzadeh, S; Coak, M; Franke, I; Goddard, P; Singleton, J; Manson, J (2011)
We present a novel susceptometer with a particularly small spatial footprint and no moving parts. The susceptometer is suitable for use in systems with limited space where magnetic measurements may not have been previously possible, such as in pressure cells and rotators, as well as in extremely high pulsed fields. The susceptometer is based on the proximity detector oscillator, which has a broad dynamic resonant frequency range and has so far been used predominantly for transport measurements. We show that for insulating samples, the resonance frequency behavior as a function of field consists of a magnetoresistive and an inductive component, originating, respectively, from the sensor coil and the sample. The response of the coil is modeled, and upon subtraction of the magnetoresistive component the dynamic magnetic susceptibility and magnetization can be extracted. We successfully measure the magnetization of the organic molecular magnets Cu(H(2)O)(5)(VOF(4))(H(2)O) and [Cu(HF(2))(pyz)(2)]BF(4) in pulsed magnetic fields and by comparing the results to that from a traditional extraction susceptometer confirm that the new system can be used to measure and observe magnetic susceptibilities and phase transitions.